A novel approach to support implementation of biosimilars within a UK tertiary hospital. Issue 1 (20th December 2019) - Saxby, Katherine; Sanghvi, Sonali; Bodalia, Pritesh N.; Ferner, Robin E.; Leandro, Maria; Urquhart, Robert; Sofat, Reecha
Abstract : Aims To assess the transfer of patients treated with originator biological therapies to biosimilar products in a large UK tertiary referral hospital reflecting practice within the National Health Service (NHS) using prospectively collected data by a hospital‐based registry administered by the Biologics Steering Group (BSG). Methods: We analysed data collected prospectively in a hospital‐based registry in a large NHS tertiary referral hospital in the UK. The registry was administered by the hospital's BSG, which considered requests for patients to remain on or revert to originator products. The registry contained prospectively collected data on patients switching therapy from an originator to a biosimilar. The data included clinical circumstances or rationale for each request, whether it was granted, and the results of clinical reviews at 3–6 months. Results: In a 12‐month period, we identified 1299 patients who could switch to the respective biosimilar and, of these, 1196 (92%) did so. Of the 260 patients taking infliximab, 250 (96%) switched to infliximab biosimilar; of the 390 patients taking etanercept 50 mg, 298 (76%) switched to etanercept 50 mg biosimilar; and of the 649 patients taking rituximab, 648 (99%) switched to rituximab biosimilar. The BSG received 39 applications: 12 (out of 39) applications were to remain on the originator and 27 (out of 39) were to switch back to the originator. Of the applications to remain on the originator 10 (out of 12) were approved. At 3–6 month review, 2 of these approvals reported continued efficacy, 3 switched to the biosimilar, 3 switched to an alternative therapy and 2 stopped treatment. Two (out of 10) applications were not approved, both applicants reported efficacy with the biosimilar at follow up. Of the 27 applications to switch back to the originator, 16 (out of 27) applications were approved. At 3–6 months, 9 (out of 16) applicants reported regain of efficacy, 6 (out of 16) reported cessation of reported adverse effects and 1 (out of 16) switched to alternative therapy. Eight (out of 27) applications were not approved, and, at point of follow up, 50% reported efficacy with the biosimilar and 50% had switched to an alternative therapy. Three (out of 27) applications were withdrawn by the clinical team as efficacy was achieved with the biosimilar. Conclusion: We have set up a system within a busy NHS clinical practice to successfully switch patients to biosimilars, and established a mechanism to guide decisions on continuing with or reverting back to the originator. Such a system could be of use more broadly within the NHS and other health care systems.